PERILAKU VOTER DALAM MEMILIH PEMIMPIN POLITIK DAN TINJAUAN ISLAM TERKAIT CIRI-CIRI PEMIMPIN - Hayat, Ainul (Reflektika, 2022)
The behavior of voters (voters) in choosing political leaders (people's representative council, regents, governors to the President) is a reflection of a country's democracy. How voters see the leader candidate, assess the focus of the issues brought by the candidate leader, to decide whether to vote or not to vote in general elections, these three are themes that need to be studied to preserve government that comes from the will of the people and in accordance with the aspirations of the people through voting (vote). ). Islam as a guiding value in living life needs to be included in this study, especially regarding the characteristics of an appropriate leader for society. Because Islam is a guide to religious values, the Islamic review in this study is not specific to political leaders, but to the characteristics of someone who deserves to be a leader in various matters. The purpose of this study is to understand problems regarding voter behavior in selecting political leaders and to describe ibrah in Islam regarding the characteristics / criteria of leaders for the community. This study found that people's behavior in selecting political leaders is heavily influenced by rational considerations and socio-cultural closeness. Meanwhile, in an Islamic review, the characteristics of a leader for the community are someone who has more capacity/competence than the community in general.